2020
DOI: 10.5614/j.eng.technol.sci.2020.52.5.6
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Alkaline Surface Treatment Effected on Flax Fibre Woven Fabric with Biodegradable Polymer Based on Mechanical Properties

Abstract:  Composites were fabricated using thin film casting and hot-pressing.  The effects of alkaline treatment on the flexural and impact properties of flax fibre reinforced polylactic acid (PLA) thin film were investigated.  Optical images of the treated flax fibres also showed improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Generally, improved mechanical properties have been reported in PLA/flax composites [20]. In a very similar study, Laziz et al [21] investigated the surface treatment of PLA/flax fiber. The authors reported better flexural strength, higher energy, and good surface properties.…”
Section: Introductionmentioning
confidence: 95%
“…Generally, improved mechanical properties have been reported in PLA/flax composites [20]. In a very similar study, Laziz et al [21] investigated the surface treatment of PLA/flax fiber. The authors reported better flexural strength, higher energy, and good surface properties.…”
Section: Introductionmentioning
confidence: 95%
“…Though the modification caused reduction in the flexural modulus of composite, the flexural strength of composite could be improved. Laziz et al 24 used the treated and un-treated polylactic acid (PLA) to manufacture flax reinforced composites. The composite, which was produced with the wet PLA, indicated higher bending resistance than dry PLA composite.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium silicate (commonly known as water glass),is a traditional stabilizer for ax ber bleaching, its structure is similar to that of a porous sponge, and it can absorb the Cu 2+ and Fe 3 + in the bleaching bath.Sodium silicate and magnesium ions form magnesium silicate, which rarely dissolves in water, and acts as a protective colloid. Under the in uence of temperature and time, the protective lm gradually decomposes, releasing HOO − in a linear rather than geometric order, so as to achieve mild bleaching(Fakin et al 2006;Laziz et al 2020). But it can form insoluble salt with Ca 2+ and Mg 2+ during the production, that is so called silica scale.…”
mentioning
confidence: 99%